1973
DOI: 10.1113/jphysiol.1973.sp010231
|View full text |Cite
|
Sign up to set email alerts
|

An inhibition of post‐ganglionic motor transmission in the mammalian vas deferens by D‐lysergic acid diethylamide

Abstract: SUMMARY1. Under certain conditions D-lysergic acid diethylamide (LSD), 10-9-10 g/ml., exerted an immediate, prolonged and slowly reversible inhibitory effect upon the post-ganglionic motor transmission in desheathed guinea-pig vas deferens preparations.2. The most critical factor influencing this action of LSD appeared to be the train length. With short trains of less than 4 or 5 pulses the twitch inhibition produced by LSD was often total. With longer trains (5-20 pulses), the degree of inhibition declined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1

Year Published

1973
1973
1979
1979

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 6 publications
1
3
1
Order By: Relevance
“…Discussion.-These results confirm and extend those of Ambache et al (1971) and Ambache, Dunk, Verney & Aboo Zar (1973); however, these workers consider that the motor innervation of the vas is non-adrenergic. The present results support the classical concept that noradrenaline is the motor transmitter in the vas deferens.…”
supporting
confidence: 90%
“…Discussion.-These results confirm and extend those of Ambache et al (1971) and Ambache, Dunk, Verney & Aboo Zar (1973); however, these workers consider that the motor innervation of the vas is non-adrenergic. The present results support the classical concept that noradrenaline is the motor transmitter in the vas deferens.…”
supporting
confidence: 90%
“…This relatively simple explanation of the origin of the first and second components of the response to a single pulse is at odds with at least two well established observations in the literature from experiments involving repetitive stimulation in rat vasa. First, reserpine or LSD, which in the present experiments reduced only the second component of the response to a single stimulus, are known to reduce the twitch or first component of the response to repetitive stimulation Ambache, Dunk, Verney & Zar, 1973;Hughes, 1973;McGrath, 1973;Gillespie & McGrath, 1974, 1975. Secondly, guanethidine, an adrenergic neurone blocking drug and which is known to block both components of the response to repetitive stimulation (Anton et al 1977), did not abolish the response to a single stimulus.…”
Section: Discussioncontrasting
confidence: 41%
“…It has been shown to be a potent agonist at presynaptic a2-adrenoceptors in the rat heart (Drew, 1976), rat vas deferens (Ambache, Dunk, Verney & Zar, 1973;Hughes, 1973), rat anococcygeus muscle and dog retractor penis muscle (Ambache, Killick, Srinivasan & Zar, 1975), but a weak agonist, or even an antagonist, at postsynaptic a1-adrenoceptors (Ambache et al, 1975;Drew, 1976). Hughes (1973) has reported that LSD inhibits the twitch response of the guinea-pig ileum by a presynaptic agonist action, which suggests that a2-adrenoceptors are involved.…”
Section: Discussionmentioning
confidence: 99%